Strategi Komunikasi Pemasaran Butanoya melalui Media Sosial Instagram - Angelique, Chelsea; Pandrianto, Nigar (Kiwari, 2024)
This study examines the use of Instagram social media for marketing communication and consumer trust-building for Butanoya Indonesia. The theory of marketing communication with kinds of marketing communication lends to credence to this research. The qualitative approach method of data collecting used in this study includes observation, interview, and documentation. Mr. Alvin Oktavian, the owner of Butanoya Indonesia, is the primary informant for this study since he can supply details regarding the subject of the research. Next comes the informant source, Mr. Aheng, who happens to be an employee. In order to support the research findings, consumers who have tried Butanoya Indonesia’s food are also included, in this case, Mr. Gregory Vincent. In addition, an expert who has experience in the field of social media, Ms. Kathleen Anastasia. The findings demonstrated that Butanoya Indonesia makes advantage of social media and marketing communication. Instagram is the social media platform that Butanoya Indonesia uses. This research focuses on consumer trust and looks for the impact and effectiveness of social media marketing communications. The results are expected to provide practical insights for certain food brands, helping them to better use social media to build consumer trust. Studi ini mengkaji penggunaan media sosial Instagram untuk komunikasi pemasaran dan membangun kepercayaan konsumen untuk Butanoya Indonesia. Teori komunikasi pemasaran dengan jenis komunikasi pemasaran memberikan kredibilitas untuk penelitian ini. Metode pendekatan kualitatif pengumpulan data yang digunakan dalam penelitian ini mencakup pengamatan, wawancara, dan dokumentasi. Bapak Alvin Oktavian sebagai pemilik Butanoya Indonesia, adalah informant utama untuk penelitian ini karena ia adapat memberikan rincian tentang subyek penyelidikan. Selanjutnya narasumber informan berupa karyawan Butanoya Indonesia yaitu Mr. Aheng. Serta konsumen sebagai pelanggan yang sudah mencicipi makanan Butanoya Indonesia untuk memperkuat hasil penelitian yaitu Kak Gregory Vincent. Selain, itu ahli pakar yang sudah berpengalaman dibidang media sosial, Kak Kathleen Anastasia. Hasil penelitian menunjukkan bahwa Butanoya Indonesia menggunakan komunikasi pemasaran dan media sosial. Media sosial yang digunakan Butanoya Indonesia adalah Instagram. Penelitian ini berfokus pada kepercayaan konsumen dan mencari dampak dan efektivitas komunikasi pemasaran media sosial. Hasilnya diharapkan dapat memberikan wawasan praktis bagi merek makanan tertentu, membantu mereka menggunakan media sosial dengan lebih baik untuk membangun kepercayaan konsumen.